Dipeptidyl-Peptidase-IV Inhibitors, Imigliptin and Alogliptin, Improve Beta-Cell Function in Type 2 Diabetes - Liu, Xu; Liu, Yang; Liu, Hongzhong; Li, Haiyan; Yang, Jianhong; Hu, Pei; Xiao, Xinhua; Liu, Dongyang (Frontiers in Endocrinology, 2021)
Objects: Imigliptin is a novel dipeptidyl peptidase-4 (DPP-4) inhibitor. In the present study, we aimed to evaluate the effects of imigliptin and alogliptin on insulin resistance and beta-cell function in Chinese patients with type-2 diabetes mellitus (T2DM). Methods: A total of 37 Chinese T2DM patients were randomized to receive 25 mg imigliptin, 50 mg imigliptin, placebo, and 25 mg alogliptin (positive drug) for 13 days. Oral glucose tolerance tests were conducted at baseline and on day 13, followed by the oral minimal model (OMM). Results: Imigliptin or alogliptin treatment, compared with their baseline or placebo, was associated with higher beta-cell function parameters (φs and φtot), and lower glucose area under the curve (AUC), and postprandial glucose levels. The changes in the AUC for the glucose appearance rate between 0 and 120 min also showed a decrease in imigliptin or alogliptin groups. However, the insulin resistance parameter (SI), fasting glucose, was not changed. For the homeostatic model assessment parameters (HOMA-β and HOMA-IR) or secretory units of islets in transplantation index (SUIT), no statistically significant changes were found both within treatments or between treatments. Conclusions: After 13 days of treatment, imigliptin and alogliptin could decrease glycemic levels by improving beta-cell function. By comparing OMM with HOMA or SUIT results, glucose stimulation might be more sensitive for detecting changes in beta-cell function.